THE ANALYSIS OF ABNORMAL RETURN, LIQUIDITY AND STOCK RISK DIFFERENCE DURING PRE AND POST STOCK SPLIT IN IDX PERIOD 2010 – 2014 - Mardiyati, Umi; Rachmattullah, Rachmattullah; Ahmad, Gatot Nazir (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2017)
This study aimed to analyze the differences of abnormal return, liquidity and risk stock before and after the stock split on companies listed in Indonesia Stock Exchange 2010 - 2014. The sample are 29 companies selected by purposive sampling. Period of observations used in this study is 5 days before the stock split and 5 days after the stock split. The analysis technique used is the Kolmogorov-Smirnov test for normality test, paired sample t-test for normally distributed data and Wilcoxon signed rank test if distribution data is not normal. Results from the study showed that there is no significant difference in abnormal returns between before and after stock split period, there are differences in liquidity between the before and after stock split period and there is no difference in stock risk between before and after the stock split period. Keywords : Stock Split, Abnormal Return, Liquidity, Stock Risk